Comparative study of congestion notification techniques for hop‐by‐hop‐based flow control in data centre Ethernet. Issue 4 (1st July 2018) - Khurshid, Waqar; Laiha Mat Kiah, Miss; Khan, Imran Ali; Salleh, Rosli; Chronopoulos, Anthony Theodore; Madani, Sajjad Ahmed
Abstract : Data centre Ethernet (DCE) is a budding research area that has received considerable attention from the ICT sector. The traditional DCEs are considered unreliable despite being widely used in modern day data centres. In Ethernet intermediate layer 2 switching devices, the outgoing traffic is faster than the incoming traffic and therefore results in packet drops. Ethernet reliability is provided by the upper layer protocols, which is outlaw to the initial concept of the network. As such, various congestion notification (CN) techniques for hop‐by‐hop‐based flow control have been proposed for layer 2 devices to address the issue of silent packet drops. However, a simulation‐based evaluation of IEEE standards that solely focus on CN techniques remains lacking. This study investigates CN techniques for layer 2 devices that employ a hop‐by‐hop‐based flow control. It also highlights the challenges confronting CN techniques in determining the optimal buffer threshold. In addition, FCoE protocol and its relation to CN are emphasized. A simulation‐based evaluation of IEEE standards (IEEE 802.3x and IEEE 802.1Qbb) is performed on a hop‐by‐hop‐based flow control with the traditional IEEE 802.3 Ethernet under different traffic loads. The parameters, such as throughput, end‐to‐end delay, and buffer space utilization, are evaluated through a simulation‐based comparison.